Extrusion Textures in Al, 6061 Alloy and 6061/SiCp Nanocomposites - Jiang, X. (2013)
The 6061 alloy matrix composites reinforced with 10wt% and 15wt% of SiC nanoparticles with an average diameter of ~500nm were hot extruded in strip shape from ball milled powders. The microstructures and textures of the hot extruded nanocomposites have been investigated by means of three dimensional orientation distribution functions and electron backscatter diffraction (EBSD) techniques. Pure Al and 6061 alloy extruded strips from atomised powders have been produced for comparison purposes. The results show that the non-deformable SiC particulates have a strong influence on the formation of extrusion textures in the matrix. Pure Al and 6061 alloy develop a typical β fibre texture after extrusion in strip shape. For 6061/SiCp nanocomposites, the intensities of major texture components decrease with increasing amount of SiC particles. The total intensities of Brass, Dillamore and S components have decreased by 19% for 6061/10wt%SiCp and 40% for 6061/15wt%SiCp composites when compared with the 6061 alloy. EBSD analysis on local grain orientations shows limited Al grain rotations in SiC rich zones, resulting in the decreased texture intensities.